Challenges, opportunities and strategy for cassava subsector development in Nigeria - Ezedinma, C.I.; Kormawa, P.M.; Manyong, Victor M.; Dixon, Alfred G.O. (2007)
Nigeria has substantial economic potential in its agricultural sector. However, despite the importance of agriculture in terms of employment creation, its potential for contributing to economic growth is far from being fully exploited. The sector's importance fluctuates with any rise and fall in oil revenue and has remained stagnant over the past ten years. The contribution of the manufacturing sector to the GDP declined over the same period. Inappropriate macroeconomic and sector policies perpetuated by the 15 years of military rule and mismanagement have had a negative impact, not only on agriculture but also on the entire economy. Presently, Nigeria grows more cassava than any other country in the world. Production has been driven primarily by the demand for food for its nearly 130 million inhabitants while very little is used for feed and industry. Estimates indicate that 52% of cassava output is wasted due to inefficiencies in production and processing, 43% is consumed as food while five percent is used as livestock feed. The question remains whether the country could reduce the amount wasted by diversifying utilisation to bring down levels of unemployment and rural poverty and enhance economic growth. Using data from primary and secondary sources, the paper assesses the challenges and opportunities in the development of the cassava sub-sector in Nigeria. At the moment, the country does not seem to have a comparative advantage in cassava exports due to inefficiencies in domestic production. There is a need to encourage product diversification to take advantage of the huge domestic and regional markets. The paper recommends a market-led strategy with an emphasis on agroindustrial development and the mobilization of resources through partnerships to improve domestic efficiency and subsequently tap into regional markets in West and Central Africa.